PENINGKATAN KOMPETENSI GURU PROFESIONAL BERBASIS PENULISAN ARTIKEL HASIL PTK BAGI GURU ANGGOTA PGRI DI KABUPATEN PURWOREJO - Suwarno Widodo; Suyoto .; Supardi .; Agus Wismanto (Universitas PGRI Semarang, 2014)
The purpose of community service activities Ib.M is to provide training and mentoring to teachers in the district Purworedjo PGRI members in order to enhance the professional development of teachers Sustainable pascasertifikasi scientific publications based on the results of PTK . The method used is the method of lecture , discussion , question and answer , the methods of training , assignment , and mentoring . The approach includes five stages are carried out systematically and continuously by stages : 1 ) the first phase , the delivery of material : ( 1 ) Technical Proposal Preparation Class Action Research , (2 ) Technical Report Preparation TOD ; ( 3 ) Techniques of Writing Action Research Results classes and ( 4 ) Rule Tata Write Journal of Advanced Research ; 2 ) the second stage , the preparation of training proposals and reports PTK; drill results TOD article preparation ; 3 ) the third stage , the implementation of TOD mentoring practices in the field , 4 ) The fourth stage , mentoring and supervising the preparation of TOD , and 5 ) the fifth stage , mentoring practices PTK compose articles results ready for publication in research journals . Outcomes generated targets are teachers : 1 ) motivated and willing to develop innovative learning in school through PTK and 2 ) make the results TOD article that is ready to be loaded and Teaching Education Research Journal Educational Insights air- ISSN 2354-5739 Volume 1 Number first issue 1 November 2013 . As a follow up , PGRI Ib.M Purworejo as partners to form a product will follow Journal of Educational Research and Teaching